Archives in 2011 - Alberch-Fugueras, Ramón (Anuario ThinkEPI, 2012)
The balance of the activity of Spanish archives in 2011 is remarkably satisfactory. Areas where improvement has led to a more relevant improvement (document management regulations, digital preservation, access, human rights) and the need for increased efforts in training, archival legislation, re-use of information and research are pointed out.